1994
DOI: 10.1073/pnas.91.15.7247
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial environment is required for activity of the cholesterol side-chain cleavage enzyme, cytochrome P450scc.

Abstract: After pregnenolone is produced in mitochondria, conversion to glucocorticoid and mineralocorticoid hormones requires both extramitochondrial and intramitochondrial enzymes. Forexample, in the synthesis ofcortisol, pregnenolone must exit from the mitochondria to undergo conversions by 3p-hydroxysteroid dehydrogenase (a non-P450 microsomal enzyme) and by microsomal P450c17 and P450c21. The resulting product, 11-deoxycortisol, must then reenter the mitochondria for conversion to cortisol by P450cll (for review, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 36 publications
4
61
0
3
Order By: Relevance
“…The oligonucleotide primers used to produce the fusion proteins (oligonucletides 5-10) introduced the sequences required to create a hydrophilic linker peptide and provided the unique restriction sites needed to assemble the fusion constructs. The length and amino acid composition of the linker peptide are based on the hinge regions of naturally occurring multidomain proteins (16) as detailed previously (7,8,17). Initially, each construct was evaluated for its ability to produce RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The oligonucleotide primers used to produce the fusion proteins (oligonucletides 5-10) introduced the sequences required to create a hydrophilic linker peptide and provided the unique restriction sites needed to assemble the fusion constructs. The length and amino acid composition of the linker peptide are based on the hinge regions of naturally occurring multidomain proteins (16) as detailed previously (7,8,17). Initially, each construct was evaluated for its ability to produce RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…reductase domains used were from both mammalian (AdRed and OR) and bacterial (P450 BM-3) systems. Previously, we demonstrated that electron equivalents are passed ef ciently to cytochrome P450s only when they are linked to the proper electron transport protein (8). Thus, the presence of the other reductase domains was predicted to reduce the likelihood of producing a functional enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early on it had been demonstrated that the acute stimulation of glucocorticoid output from the adrenal gland by ACTH is sensitive to protein synthesis inhibitors (Ferguson 1963). Further studies identified steroidogenic acute regulatory protein (StAR) to initiate the cascade of steroid biosynthesis with the translocation of cholesterol from the outer to the inner mitochondrial membrane (Black et al 1994, Clark et al 1994, Spat & Hunyady 2004. StAR expression is enhanced by ACTH and Ca 2C mediated stimuli such as angiotensin II (ANGII) and potassium (Spat & Hunyady 2004).…”
Section: Introductionmentioning
confidence: 99%